The lost years of visual literacy. Issue 1 (2nd January 2021) - Peña, Ernesto; Dobson, Teresa M.
Abstract: Until today, the most accepted notion about the coinage of visual literacy as a concept has been credited to John Debes in the late 1960s. In this paper, the authors describe the use of available digital tools to unearth a history of the concept of visual literacy in education that precedes in roughly 30 years these events. These overlooked years shed light on the role of technology, policy and industrial intervention have played in the development of a concept that has only increased in relevance and popularity within education over the last decades. This paper also invites the reader to consider the potential of previously unavailable tools to revisit and re-examine the events that have shaped and will continue to shape the landscape of education.